2011
DOI: 10.1534/genetics.110.120998
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for Antagonism Between Pak Protein Kinase and Rho1 Small GTPase Signaling in Regulation of the Actin Cytoskeleton During Drosophila Oogenesis

Abstract: During Drosophila oogenesis, basally localized F-actin bundles in the follicle cells covering the egg chamber drive its elongation along the anterior-posterior axis. The basal F-actin of the follicle cell is an attractive system for the genetic analysis of the regulation of the actin cytoskeleton, and results obtained in this system are likely to be broadly applicable in understanding tissue remodeling. Mutations in a number of genes, including that encoding the p21-activated kinase Pak, have been shown to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 111 publications
2
20
0
1
Order By: Relevance
“…A requirement for Pak in basal stalk cell intercalation is consistent with its established roles in regulating the actin cytoskeleton during cell shape change and motility (Bokoch, 2003). We have shown that Pak regulates actomyosin contractility during development of the follicular epithelium, and it is possible that misregulation of contractility underlies the Pak basal stalk phenotype (Vlachos and Harden, 2011). We assessed the status of actomyosin contractility in basal stalks by staining for phosphorylated myosin light chain ( pMLC), which reveals active myosin.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…A requirement for Pak in basal stalk cell intercalation is consistent with its established roles in regulating the actin cytoskeleton during cell shape change and motility (Bokoch, 2003). We have shown that Pak regulates actomyosin contractility during development of the follicular epithelium, and it is possible that misregulation of contractility underlies the Pak basal stalk phenotype (Vlachos and Harden, 2011). We assessed the status of actomyosin contractility in basal stalks by staining for phosphorylated myosin light chain ( pMLC), which reveals active myosin.…”
Section: Resultsmentioning
confidence: 69%
“…Normally, this cannot be addressed owing to the degradation of all Pak chambers at around stage 10 (Conder et al, 2007); however, as we previously demonstrated, heterozygosity for any component of the Rhoactivated actomyosin contractility pathway suppresses this degradation (Vlachos and Harden, 2011). Heterozygosity for an allele of Rho1 enabled a small number of Pak mutant paired-egg chambers to develop into fused mature eggs, complete with dorsal appendages (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Genetic screens, on the other hand, could be used to either identify genes, which when mutated in follicle cells, lead to round eggs, or genes, which when mutated in combination with a previously identified round egg gene, lead to the suppression or enhancement of the round egg mutant phenotype. Both of these genetic screen approaches have been recently used to identify additional proteins that contribute to egg chamber elongation, although detailed characterization of the roles of most of these genes has not yet been performed 44 , 73 . Even with the completion of these recent screens, it is unlikely that all of the genes that contribute to egg chamber elongation have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Since these fibers are anchored at either end by focal adhesions that connect them to the ECM, their contraction results in the generation of traction forces which help pull the cell forward 79 . In follicle cells, the activated form of non-muscle Myosin II is present at the basal surface starting at stage 7 44 , 80 . This suggests that contraction of the basal actin filaments may be involved in generating the force necessary to mediate follicle cell migration during egg chamber rotation.…”
Section: Insights Into the Mechanism Of Egg Chamber Elongationmentioning
confidence: 99%